Abnormal grain growth in a Zn-0.8Ag alloy after processing by high-pressure torsion. (1st April 2021) - Bednarczyk, Wiktor; Kawałko, Jakub; Rutkowski, Bogdan; Wątroba, Maria; Gao, Nong; Starink, Marco J.; Bała, Piotr; Langdon, Terence G.
Abstract: Abnormal grain growth (AGG) in a Zn-0.8Ag (wt%) alloy, produced through the application of high-pressure torsion (HPT), was systematically investigated using scanning electron microscopy (SEM), electron backscattered diffraction (EBSD), high-resolution transmission electron microscopy (HR-TEM) and microhardness testing. The HPT-deformed alloy exhibits AGG at room temperature without any additional heat treatment. Analysis by EBSD revealed oriented grain nucleation in a { 11 2 ¯ 0 } 〈 0001 〉 direction from the initial ( 0001 ) fibre texture which agrees with the maximum energy release model. New grains were oriented according to the minimal Young's modulus direction (c-axis), parallel to the shearing direction. The strain-induced dissolution of nanocrystalline Zn3 Ag precipitates was identified as the main driving force for AGG in this alloy. The strains necessary for the initiation and termination of AGG were determined as ~4.0 and ~5.0, respectively. The increase in solid-solution strengthening caused an increase in hardness from ~47 HK in the fine-grained centre to ~84 HK in the coarse-grained region. A Hall-Petch investigation revealed grain refinement softening below a grain size of 23 µm. These results provide the first comprehensive description of AGG in metallic materials processed by a severe plastic deformation method at room temperature. Graphical abstract: Image, graphical abstract